The Research of the Evolution and Dialectical Development of the Balance Sheet`s Structure and Contents in Russia - LIDIYA I. Kulikova; LEISAN R. Adgamova (Учёт. Анализ. Аудит)
The article is devoted to the study of changes in the balance sheet`s structure and contents in Russia in historical aspect. The research is based on the studies of the early twentieth century scientists specializing in accounting such as A. M. Gavrilov, N. S. Arinushkin, A. K. Roschahovsky, A. M. Galagan, J. M. Halperin, I. A. Koshkin. The directions of research were defined on the basis on the balance sheet dialectical study, developed by professor J. M. Halperin in his paper “Essays on the theory of balance sheet” written in 1930. The research of the balance sheet`s structure and contents is based on the following statements: continuous balance sheet variability, general conditioning of occurrence, contradictory development of a balance sheet, abrupt discontinuity of balance sheet`s processes. When writing the article, the authors used the sources not widely referred to in papers about the history of accounting development in Russia. The article reveals the analytical capacity of the balance sheet`s contents to make specific conclusions regarding the financial position of the company. The article deals with a wide range of issues: changes of balance sheet`s contents with the development of economics, the order of arranging the items, balance sheet`s items evaluation, the balance sheet`s classification depending on the purpose of its preparation, necessity of forming the indicators of a balance sheet for public presentation. The authors conclude that the balance sheet`s structure and contents depend on the specific historical conditions and is influenced by external economic and political environment. A balance sheet in Russia now is the result of over one- century evolution comprising several stages each being closely related to the changes in the country`s economic life.